Information Systems And Capabilities Auditors Investigative To Effectiveness Implementation Audit Procedure In Proving Fraud (Case Study of the Regional Inspectorate of Karo Regency) - Septony B Siahaan; Arthur Simanjuntak; Wesly A Simanjuntak; Mulatua P Silalahi; Depi Erosna Br Tarigan (Program Studi Akuntansi Universitas Simalungun, 2023)
This study aims to examine and analyze the effect of accounting information systems and the ability of investigative auditors on the effectiveness of implementing audit procedures in proving fraud . this research is descriptive statistical analysis, data quality test, classical assumption test, multiple linear regression and hypothesis testing. The independent variables in this study are the flow of accounting information systems and the ability of investigative auditors while the dependent variable is the effectiveness of the implementation of audit procedures in proving fraud. The total population in this study was 47 with use purposive sampling . This study uses primary data. The data analysis used was multiple linear regression with Microsoft Excel and software programs Statistical Package for the Social Sciences (SPSS) 25. The results of this study prove that simultaneously the accounting information system and the investigative auditor's ability have a significant effect on the effectiveness of implementing audit procedures in proving fraud. the effectiveness of the implementation of audit procedures in proving fraud . Study This is the development of research previously by proving that accounting information systems and the ability of investigative auditors influence the effectiveness of the implementation of audit procedures in proving fraud. Study done at the Regional Inspectorate of Karo Regency